Life History Trade-offs associated with Evolution of Cancer - Worsley, Catherine Mary (University of the Witwatersrand, Johannesburg, 2023)
The evolution of multicellularity requires cooperation between single cells to form new multicellular individuals. Changes in levels of selection occur during this process, with selection at the multicellular level overriding that at the single cell level. For a multicellular individual to function, somatic mutations and selection must be under tight regulation. Nevertheless, mutations and selective environmental pressures can select for cells with fitness advantages relative to normal cells, resulting in cancer. Therapeutic drugs and radiation are forms of artificial selection that can drive the development and selection of cell populations that are resistant to treatment. Cancer occurs because of the failure of multicellular systems to suppress somatic evolution. This somatic evolution results in tumour cells with a wide range of phenotypes with either fast (proliferating) or slow (quiescent) life history strategies. Evolutionary theory provides a framework for understanding what drives the formation of these phenotypes and the ecological niche that supports them, and helps in predicting tumour progression and response to therapy. The key hypothesis of this study was that selective pressures in the tumour microenvironment drive trade-offs between tumour cell survival, proliferation, and apoptosis. An extensive literature review was conducted to identify key selective pressures affecting tumour progression. Low extracellular pH was identified as a component of the tumour microenvironment that affects life history trade-offs, and particularly drives escape from immune-mediated destruction. A protocol was then developed to expose cancer cells to low pH in cell culture. Breast carcinoma and oesophageal squamous cell carcinoma cell lines were selected for these experiments based on the prevalence of these cancers and because of their different anatomical locations. Exposure to low pH induced different levels of apoptosis in each cell line. This also affected cell cycle progression and the secretion of growth factors and immunomodulatory cytokines. The oesophageal cell line, WHCO6, adapted to moderate acidity levels with some cells undergoing apoptosis. Factors released by these cells supported the growth and survival of related cells. In contrast, in the breast carcinoma MCF-7 cell line, low pH induced high rates of apoptosis, and factors released by dying cells stimulated death in related cells. This study highlights that different life history strategies are employed by different cancer types. It also shows the importance of the tumour microenvironment, and acidity in particular, in driving tumour cell adaptation and survival. This study also identifies apoptosis as a pro-tumorigenic driver of cancer progression which has important therapeutic implications.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy, to the Faculty of Health Sciences, School of Pathology, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Cancer; Cytokines; Programmed cell death; Life-history trade-offs; Evolution; UCTD; SDG-3: Good health and well-being; SDG-4: Quality education